Diagnostic Significance Vasoendothelial Growth Factor Depending on the Severity and Duration of Atopic Dermatitis, as Well as Taking into Account the Presence of Markers of Herpes Virus Infection - N. А. Imanverdiyeva; O. A. Bashkina (SINAPS LLC, 2024)
Currently, the problem of diagnosis and treatment of diseases associated with disorders of the angiogenesis process, as well as regenerative processes, is acute. Factors regulating the processes of angiogenesis in allergic diseases, including atopic dermatitis, play a key role in maintaining chronic inflammation and can have a significant impact on the course of the disease.   Materials and methods: The study is analytical cross-sectional and presented by a comprehensive examination of 140 patients with AtD aged 2 to 12 years (median age 4.2 years), divided into 2 groups: 70 children with an established diagnosis of AtD; 70 children with atopic dermatitis infected with herpes simplex virus (AtD+HVI). The control group consisted of 70 somatically healthy children. A special laboratory examination included the determination of specific IgM and/or IgG class antibodies to herpes simplex virus type 1-2 antigens by enzyme immunoassay (ELISA); determination of the DNA of the studied herpesviruses in blood samples by polymerase chain reaction; determination of vascular endothelial growth factor A (VEGF-A) in the blood plasma of patients by ELISA.   The results of our own research: A statistically significant (p <0.001) increase in the level of vascular endothelial growth factor A in blood serum was found in children with AtD compared with the control group. Against the background of infection with the herpes simplex virus, an increase in the level of vascular endothelial growth factor A in blood serum was revealed compared with patients with atopic dermatitis (p < 0.001). There was also a statistically significant increase in serum VEGF-A levels in patients with AtD (p < 0.001) and AtD+HVI (p < 0.001) with an increase in the severity of AtD. This was confirmed by the results of a correlation analysis that revealed the relationship between the level of VEGF-A and the severity of clinical symptoms of the disease.The addition of herpesvirus infection to AtD worsens the clinical symptoms of this disease.